Discovering the Right to Criminal Disclosure: Lessons from Civil Procedure - WONG, Denise Huiwen (Institutional Knowledge at Singapore Management University, 2013)
The amendments to the Criminal Procedure Code (Cap 68, 1985 Rev Ed) and subsequent case law developments have created a patchwork of rules governing the disclosure obligations of parties in criminal cases. This article argues that parties have thereby been endowed with a right that is exercisable in the courts to access the material to which the law says they are entitled. However, there are currently no proper procedural mechanisms in place for parties to make interlocutory applications to obtain such material. This article examines the competing values and ideals of a criminal discovery regime, and suggests that concepts such as further and better particulars and specific discovery can be adapted from the rules of civil procedure to create an overarching framework that can regulate applications to the court for access to materials prior to trial.